Pengaruh Media Baamboozle Terhadap Minat Belajar Matematika Siswa di MI Nurul Huda - Aulia, Ghina; Amran, Amran; Saputra, Raden Ridwan Hasan (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study aims to examine the effect of Baamboozle learning media on the interest in learning Mathematics of class II students of MI Nurul Huda 3 Bogor. The method used is quantitative with a Quasi Experimental design, specifically Nonequivalent Control Group Design. The sample consisted of 42 students, divided into two groups: the experimental class (using Baamboozle) and the control class (without Baamboozle), 21 students each, selected through purposive sampling. The research instrument was a learning interest questionnaire. The results showed that the average posttest of the experimental class (46.8) was higher than the control class (36.5), with a significance value of 0.000 (<0.05), indicating that Ha was accepted. In conclusion, Baamboozle media has a significant effect on increasing students' interest in learning Mathematics